Manusia, Agama, dan Masyarakat: Suatu Wacana Menuju Dialog Multi-peradaban Global - Togardo Siburian (Societas Dei: Jurnal Agama dan Masyarakat, 2014)
ABSTRACT: This article tries to foster a multi-civilization dialogue to religious society that faces humanity crisis due to extremism. Study through library research found that there is an axiom that religion and society is necessity in human life. In realty this two dimension is closely related and may resulted in sharp conflicts between culture and civilization. Inter-religious studies, including inter-religion dialogue, are developed to overcome these conflicts. Unfortunately the differences in comparative religious study are widened, although in the hazy form such as multi-culturalism ideas wich contain interreligious aspect. The ideas of multi-religionism in the intra and inter-religion dialogue become an important principe, since it looks upon One God as a source of religious existence in human. It is necessery to exceep the multi-religion principe wich deals with other factors such as race, culture, social, politics, economy, technology, and education of modern person. An innovative concept is neeeded that combines all existing elements in global multi-civilization dialogue, by considering global factors such as human rights, democracy, civil society, and world ethics. This universal multi-civilization concept can be declared as a discourse to overcome crises today comprehensively. KEYWORDS:Â human, society, inter-religion, global, civilization, dialogue, multi-civilization, present